2011
DOI: 10.1111/j.1365-294x.2011.05258.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent long-distance transgene flow into wild populations conforms to historical patterns of gene flow in cotton (Gossypium hirsutum) at its centre of origin

Abstract: Over 95% of the currently cultivated cotton was domesticated from Gossypium hirsutum, which originated and diversified in Mexico. Demographic and genetic studies of this species at its centre of origin and diversification are lacking, although they are critical for cotton conservation and breeding. We investigated the actual and potential distribution of wild cotton populations, as well as the contribution of historical and recent gene flow in shaping cotton genetic diversity and structure. We evaluated histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 61 publications
6
86
0
1
Order By: Relevance
“…Several studies have shown that gene flow from transgenic to wild plants has already occurred. For example, Wegier et al (2011) confirmed the presence of transgenes in wild cotton plants in Mexico, which is the center of origin of this species. In this case, the evolutionary costs of this introgression should be evaluated, while a general question should be addressed: What would be the economic cost of losing the populations that gave rise to different crops used in agriculture today?…”
Section: Conclusion and Future Researchmentioning
confidence: 66%
“…Several studies have shown that gene flow from transgenic to wild plants has already occurred. For example, Wegier et al (2011) confirmed the presence of transgenes in wild cotton plants in Mexico, which is the center of origin of this species. In this case, the evolutionary costs of this introgression should be evaluated, while a general question should be addressed: What would be the economic cost of losing the populations that gave rise to different crops used in agriculture today?…”
Section: Conclusion and Future Researchmentioning
confidence: 66%
“…Outcrossing has been measured at distances of up to 1,625 m [21]. Thus, the findings of Wegier et al [16] showing that outcrossing has taken place are not entirely surprising. A potential cause for the spread of transgenic cotton could probably be the transport of cotton seed from the USA, which is used as livestock feed.…”
Section: Case Study: Transgenic Cotton In Mexicomentioning
confidence: 94%
“…Based on genetic differences, eight metapopulations can be distinguished. In a pilot study published in 2011 [16], Wegier et al were able to show that transgene constructs from genetically engineered cotton have spread into these populations. Genetically engineered cotton has been planted in Mexico since 1996.…”
Section: Case Study: Transgenic Cotton In Mexicomentioning
confidence: 99%
“…The possible sources and routes by which the genetic constructs might have arrived are unknown, this is also true in relation to the effects and consequences they might represent, targeted research is underway. Up to now, neither the proponents nor the competent authorities have openly reacted to the fi ndings [ 9 ] or to the warnings made by some scientifi c institutions (such as CONABIO has in its risk assessments).…”
Section: Biosafety Levelsmentioning
confidence: 95%
“…In the case of GM cotton (level III), the fact is that recombinant proteins expressed from genetic constructs of GM cotton events have been detected in at least half the wild tetraploid cotton metapopulations present in Mexico [ 9 ]. The possible sources and routes by which the genetic constructs might have arrived are unknown, this is also true in relation to the effects and consequences they might represent, targeted research is underway.…”
Section: Biosafety Levelsmentioning
confidence: 98%